Examining the influence of leadership behavior and decision - making on employee performance in ninprofit organization case study at yayasan idh - Putri Wardhani, Yashinta; Welly, John (The Indonesian Journal of Business Administration, 2018)
Abstract – Yayasan IDH is a small scale nonprofit organization who work and doing projects in Indonesia to tackle environmental issue related to agriculture commodities and estate crops. Yayasan IDH relatively is a new established entity which newly operated, with total 22 employees and in parallel also need to developed procedures and policies including human resource system, to achieve operational excellent. With the rapid employee growth in the last two years, Yayasan IDH will also need to strengthen its position as an organization including its human resource management. Using the modified Kouzes – Posner approach, leadership assessment at Yayasan IDH would like to capture the leadership and decision – making individual behavior and its influence on employee performance. The leadership assessment expected to address issue concerning leadership behavior and decision – making behavior and give recommendation to the discovered issue. Keywords:  decision making, employee performance, human resource, leadership, nonprofit organization